PENGARUH RASA CEMAS TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA DI SMP NEGERI 28 MEDAN - Machrani Adi Putri Siregar; Eryanti Lisma (State Islamic University of North Sumatra, 2018)
This study entitled The Effect of Anxiety on Students' MathematicsLearning Achievement in SMP Negeri 28 Medan. In this study,anxiety as an independent variable and mathematics learningachievement as the dependent variable. Anxiety when learningmathematics possessed by students tends to be influenced by theimage of mathematics lessons that are already known to befrightening. This is because students recognize mathematicssubjects are difficult and complicated subjects, so that it triggersfear of students to learn mathematics and cause anxiety when facedwith mathematics. Based on the theory, there are many factors thatinfluence students' mathematics learning achievement. In thisstudy, researchers took the anxiety factor above. This research tookplace at SMP Negeri 28 Medan, which was located at Jl. KaryaBersama No. 17 Medan Johor. The research method used in thisstudy is a quantitative method with a sample of all eighth gradestudents totaling 273 students and divided into 8 (eight) studygroups. Data taken in the form of questionnaires and analyzedusing simple linear regression analysis. Data analysis wasperformed using SPSS 21 software for Windows. From the resultsof this study, it was concluded that there was no effect of anxietyon students' mathematics learning achievement. Or in other words,students' mathematics learning achievements are not at all affectedby the students' anxiety in facing exams, especially in mathematics.